Application of Cow Manure Compost to Improve Growth and Yield of Paddy Rice (Oriza sativa L.) Mahsuri Variety - Maruapey, Ajang; Ali, Akhmad (Agrikan Jurnal Agribisnis Perikanan, 2023)
Rice plants from planting to production really need nutrients to increase production optimally. The application of cow dung compost fertilizer aims to prove the effect of treatments with different doses on the growth and production of mahsuri rice varieties. Research on the application of cow dung compost fertilizer was carried out in Makbalim village, Mayamuk District, Sorong Regency, Southwest Papua. The experiment was conducted from May to October 2023. The experiment used Randomized Group Design (RAK) with 4 levels of dose treatment namely; B0 = 0 kg (without fertilizer), B1 = 4 kg plot-1, B2 = 6 kg plot-1, B4 = 8 kg plot-1. Research data were analyzed using variance analysis (anova). If the research data is significantly different, it is continued with BNT test at 0.5% confidence level. The results showed that the treatment dose of 6 kg plot-1 affected the total number of tillers, the number of productive tillers, the total number of grains and GKP production, while the treatment dose of 8 kg plot-1 was able to increase plant height and 1000-grain weight. The best treatment with the optimal dose of 6 kg plot-1 was able to increase the highest dry grain production (GKP) reaching 6.30 tons/ha.